Comparative Analysis of the Recent Financial Crisis' Impact on the Retail Electronic Commerce in the European Union in the USA and in Poland; Analiza komparatywna wpływu ostatniego kryzysu finansowego na detaliczny handel elektroniczny w Unii Europejskiej, w Stanach Zjednoczonych Ameryki oraz w Polsce - Tomasz Czajkowski (Comparative Economic Research. Central and Eastern Europe, 2011)
The aim of this article is to compare and assess the impact of the recent financial crisis on the retail electronic commerce in the economies of the European Union, the USA and Poland. Therefore the selected data from the biggest international companies connected with the retail electronic commerce from the years 2007 and 2008 in comparison to the previous year, and the selected economic data from the economies of the USA, the European Union and Poland till the year 2009, concerning the utilization and value of the electronic commerce trade and the number of people doing shopping online, and conclusions drawn from the analyses of those data are presented and discussed. – – Celem artykułu jest poroẃnanie oraz ocenienie wpływu ostatniego kryzysu finansowego na detaliczny handel elektroniczny w gospodarkach Unii Europejskiej, Stanoẃ Zjednoczonych oraz Polski. W tym celu wybrane dane z najwiekszych miedzynarodowych firm zwiazanych z detalicznym handlem elektronicznym z lat 2007 i 2008 w poroẃnaniu do roku poprzedniego oraz wybrane dane ekonomiczne z gospodarek Stanoẃ Zjednoczonych, Unii Europejskiej i Polski do roku 2009, dotyczace wykorzystatnia oraz wartosći detalicznego handlu elektronicznego i liczby ludzi korzystajacych z zakupoẃ internetowych oraz wnioski wyciagniete z analiz tych danych sa zaprezentowane i omoẃione.
Keywords: 330